Impact of Sociodemographic Disparities and Insurance Status on Survival of Patients with Early‐Onset Colorectal Cancer. (5th August 2021) - Salem, Mohamed E.; Puccini, Alberto; Trufan, Sally J.; Sha, Wei; Kadakia, Kunal C.; Hartley, Marion L.; Musselwhite, Laura W.; Symanowski, James T.; Hwang, Jimmy J.; Raghavan, Derek
Abstract: Background: Low socioeconomic status (SES) has been linked to worse survival in patients with colorectal cancer (CRC); however, the impact of SES on early‐onset CRC remains undescribed. Materials and Methods: Retrospective analysis of data from the National Cancer Database (NCDB) between 2004 and 2016 was conducted. We combined income and education to form a composite measure of SES. Logistic regression and χ 2 testing were used to examine early‐onset CRC according to SES group. Survival rates and Cox proportional hazards models compared stage‐specific overall survival (OS) between the SES groups. Results: In total, 30, 903 patients with early‐onset CRC were identified, of whom 78.7% were White; 14.5% were Black. Low SES compared with high SES patients were more likely to be Black (26.3% vs. 6.1%) or Hispanic (25.3% vs. 10.5%), have T4 tumors (21.3% vs. 17.8%) and/or N2 disease (13% vs. 11.1%), and present with stage IV disease (32.8% vs. 27.7%) at diagnosis ( p < .0001, all comparisons). OS gradually improved with increasing SES at all disease stages ( p < .001). In stage IV, the 5‐year survival rate was 13.9% vs. 21.7% for patients with low compared with high SES. In multivariable analysis, SES (low vs. high group; adjusted hazard ratio [HRadj ], 1.35; 95% confidence interval [CI], 1.26–1.46) was found to have a significant effect on survival ( p < .0001) when all of the confounding variables were adjusted. Insurance (not private vs. private; HRadj, 1.38; 95% CI, 1.31–1.44) mediates 31% of the SES effect on survival. Conclusion: Patients with early‐onset CRC with low SES had the worst outcomes. Our data suggest that SES should be considered when implementing programs to improve the early detection and treatment of patients with early‐onset CRC. Implications for Practice: Low socioeconomic status (SES) has been linked to worse survival in patients with colorectal cancer (CRC); however, the impact of SES on early‐onset CRC remains undescribed. In this retrospective study of 30, 903 patients with early‐onset CRC in the National Cancer Database, a steady increase in the yearly rate of stage IV diagnosis at presentation was observed. The risk of death increased as socioeconomic status decreased. Race and insurance status were independent predictors for survival. Implementation of programs to improve access to care and early diagnostic strategies among younger adults, especially those with low SES, is warranted. Abstract : The incidence of and mortality from early‐onset colorectal cancer (CRC) is on the rise. This article details the relationship between socioeconomic status and clinical outcomes of young adults with early‐onset CRC.